The Significance of the white Ccolor in the Diwan of Safi al-Din al-Hali (750 AH - . Salman Muhammad (Journal of College of Education, 2023)
The research addresses the colors contained in the Poetry collection of Safi al-Din al-Hali, relying on the close association and dialectic relationship between poetry and other arts, and the research stopped at the explicit and direct white color, and showed us the importance of the direct color uses made by the Hali, and their effectiveness in the poetic context Because of its close associations with the experience of the poet, who sought to employ color effectively, and to use it artistically to highlight his aesthetic in the poetic text, because the color has a linguistic code, and a special qualitative composition, which exercises its hobby in the production of the game of meaning.. Hence the importance of this research in identifying the white connotations of Hali in his poems.